The Friendship House Community: Christian Community as a Lived Framework for Theological Education - Thompson, L. S. Carlos A. (Journal of disability & religion, 2021)
The author briefly presents and seeks to interrogate enduring biases present within the dominant framework for engaging in Western Christian theological education. Readers are introduced to the Friendship House Community in Holland, Michigan, as a lived into context for critically engaging questions around faithful Christian life and theological education. In the process, readers are invited to boldly reconsider oft-unexamined questions such as, what exactly is the telos of faithful Christian theological education? Similarly, who ought to serve as both the intended audience of, and understood participant in, theological education? Moving beyond a framework for theological education that focuses primarily on training the pastor, the Friendship House Community is presented as a context in which the telos of Christian theological education is faithful discipleship. From here, then, theological education is presented as that which all who are in Christ ought to participate in themselves and beckon others into. Thus, the author challenges theological educators and pastors to expand our understanding of who the “students” of theological education are, and to consider a more communally embodied pedagogy. A framework for theological education in which each member of the Body of Christ—of which the pastor-in-training is only one part—is understood to be a participant. The author then moves to demonstrating this alternative educational framework in action. This is done through theologically reflecting on the author’s friendship, and mutual discipleship lived out alongside of, one of the Friendship House Community’s founding residents. Within the broader context of the Friendship House Community as a whole, then, discipleship amid shared Christian friendship is offered as a new locale for living into the telos of faithful Christian theological education.